The Deaf Community's Attitudes Towards Islamic Education - Abd. Hakim Mohad @ Mohamad Ramli; Ros Aiza Mohd Mokhtar; Nizaita Omar; Zulkifly Muda (International Journal of Arts and Sciences, USA, 2024)
Based on the review of past PMR results (the lower secondary school examinations) of the deaf community on Islamic Education in Malaysia, their achievement in the subject is relatively poor, which lends a general observation that the deaf community is lagging behind when it comes to religious development. Thus, this study aims to explore the attitude of the deaf community towards religious education. A self-administrated questionnaire was distributed to 80 respondents from the Special Education School (Deaf), Kota Kinabalu and the Centre for Deaf Activity, the Deaf Welfare Association of Terengganu. The findings of this study reveal that the deaf communitys attitude towards religious education is positive. However, their results are not on par with the non-deaf in the same examination. The findings provide information to the government agencies to improve the existing education system for the deaf. At the same time, the deaf association, other NGOs and the Malaysian society can benefit from the findings of this study to enhance their programmes and activities for the deaf.